BEDSIDE MANNERS: DO WE CARE? - Farooq, Zerwa; Mustafa, Tajammal; Akram, Alia; Khan, Mariha; Amjad, Rabbia; Naveed, Maryam; Azhar, Ayesha; Chaudhry, Abdul Majeed; Khan, M Amir Zaman; Rafiq, Farida (Journal of Ayub Medical College Abbottabad, 2013)
Background: Teaching bedside manner might prove to be one of the most challenging tasks in medical education as it is not easy to structure or formalise such training. Besides, the rigorous training process for acquiring clinical and technical skills often overshadows the humanistic aspect of medical care. The aim of this study was to assess the perception of final year medical students as well as the faculty regarding the teaching and practice of bedside manner including a brief evaluation of students' bedside manner. Methods: A cross-sectional study was conducted involving final year medical students from five medical colleges (n=193) and faculty from a single institution (n=29). Sample was selected using systematic random or convenient sampling techniques. Data was collected using self administered, anonymous, structured questionnaire. Data were analysed using SPSS-17. Results: While evaluating students' bedside manner, 85% of the students reported they always take consent while interacting with a patient whereas, only 17% of the faculty members agreed with this. Only 3% of the faculty members reported that students take care of privacy of patients and none of them thought that students reassure a patient during an encounter whereas the percentages among students were 76% and 48%, respectively. Though students thought they need to improve, majority (56%) of them was confident of their bedside manner. On the other hand, 83% of the faculty members rated students' bedside manner from fair to poor. A large proportion (69%) of the faculty members were not satisfied with the quality of teaching regarding bedside manner, reporting lack of focus on this particular aspect of medical care as the most important cause. Majority of the students (87%) believed doctors have a better bedside manner in private as compared to public hospitals. Conclusion: Students have an inflated evaluation of their bedside manner but majority felt a need to improve. A sharp contrast exists between students' and faculty's opinion regarding the practice of bedside manner by students. An outright lack of focus on bedside manner was reported as the most important cause for inadequate emphasis on teaching this particular aspect of medical care. Keywords: Bedside manners, medical care, medical education, medical student, consent, ethics